2020
DOI: 10.1071/rj20046
|View full text |Cite
|
Sign up to set email alerts
|

Missing shots: has the possibility of shooting wolves been lacking for 20 years in France

Abstract: Wolves were exterminated in France in the late 19th and early 20th centuries. Therefore, livestock breeders and herders were unprepared when wolves arrived from Italy in 1993, the year after France committed to the European Union (EU) to protect wolves. Today, ~580 wolves, whose numbers are growing exponentially, are present in over one-third of France. During the last 10 years, livestock deaths from wolves have grown linearly from 3215 in 2009 to 12451 in 2019, despite France implementing extensive damage pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
16
0
6
Order By: Relevance
“…While nonlethal mechanisms have proved effective in location A, wider application, research, and innovation (for instance technological solutions) are needed to illustrate their viability under conditions such as those in location B (Eklund et al, 2017;GCG, 2018). For instance, a study from the Alps, which have similar conditions (abrupt topography, small and scattered flocks, and high tourists numbers), showed that damage continued to increase despite widespread implementation of guardian dogs and enclosures, since wolves had adapted their hunting patterns (Meuret et al, 2021). There was also weak support for these measures among cattle farmers, such as those in location B and C, since they would imply drastic changes in husbandry regimes.…”
Section: A Systems Perspective Of the Conditions Of Human-wolf Coexistencementioning
confidence: 99%
“…While nonlethal mechanisms have proved effective in location A, wider application, research, and innovation (for instance technological solutions) are needed to illustrate their viability under conditions such as those in location B (Eklund et al, 2017;GCG, 2018). For instance, a study from the Alps, which have similar conditions (abrupt topography, small and scattered flocks, and high tourists numbers), showed that damage continued to increase despite widespread implementation of guardian dogs and enclosures, since wolves had adapted their hunting patterns (Meuret et al, 2021). There was also weak support for these measures among cattle farmers, such as those in location B and C, since they would imply drastic changes in husbandry regimes.…”
Section: A Systems Perspective Of the Conditions Of Human-wolf Coexistencementioning
confidence: 99%
“…Les modalités concrètes de sa mise en oeuvre pour assurer son efficacité soulève de nombreuses questions. L'enjeu est important face aux pertes liées à la prédation en élevage par des loups, ayant présenté en France une croissance d'allure linéaire (+ 1000 animaux tués par an) entre 2009 et 2019 (Meuret et al, 2020), avec un total de 12 451 animaux tués en 2019, dont 90 % pour les Alpes et la Provence (Dreal AURA, 2020). L'élevage ovin est particulièrement touché, représentant 90 % des pertes.…”
Section: Introductionunclassified
“…estives, grands espaces non clôturés, ont été les premiers touchés par la prédation (Vincent, 2011). Les dispositifs d'action publique se sont succédés en France depuis 1997, visant à limiter les dégâts de la prédation (Meuret et al, 2017(Meuret et al, , 2020. Ils se sont d'abord focalisés sur ces troupeaux d'estive, avec la mise en oeuvre de plusieurs moyens de protection : regroupement nocturne en enclos, renforcement de la présence humaine et utilisation de chiens de protection.…”
Section: Introductionunclassified
“…The practical modalities to ensure its effective implementation raise several questions. The stakes are high, given the amount of losses from wolf depredation on livestock, which in France has shown a linear increase (+ 1000 killed animals per year, all species considered) between 2009 and 2019 (Meuret et al, 2020), with a total of 12,451 livestock killed in 2019, 90% of which were in the Alps and Provence (Dreal AURA, 2020). Sheep farming is particularly affected, accounting each year for 90% of the total losses in France.…”
mentioning
confidence: 99%
“…wide unfenced areas, were the first to be affected by wolf predation (Vincent, 2011). As a consequence, starting in 1997, a series of national management plans and their sets of protective means aiming at limiting predation (Meuret et al, 2017(Meuret et al, , 2020, first focused on summer high-mountain pastures and large collective sheep flocks. They have encouraged the implementation of three protection means: systematic grouping of livestock in electrified night pens, supplementary human presence day and night, and guard dogs.…”
mentioning
confidence: 99%